INTERNALISASI NILAI-NILAI AYAT MAKKIYAH DAN MADANIYAH DALAM MODEL DAKWAH DI PAMEKASAN - Achmad Muzammil Alfan Nasrullah; Moh. Zahid (Bayan lin-Naas : Jurnal Dakwah Islam, 2025)
This study is motivated by the need to gain a deeper understanding of the main values of Makkiyah and Madaniyah verses in a socio-historical context and their relevance to the social, cultural, and religious dynamics of the Pamekasan community. The research problem focuses on how the values contained in these two types of verses can be adapted and implemented in local da'wah practices. The objectives of this study are: (1) to describe the main values of the Makkiyah and Madaniyah verses from a socio-historical perspective, (2) to analyze the relevance of these values to the social, cultural, and religious life of the Pamekasan community through Fazlur Rahman's double movement theory, and (3) to formulate theoretical and practical contributions to the development of a contextual and transformative model of local Islamic da'wah in Pamekasan. The approach used in this study is qualitative-descriptive with a hermeneutic-sociological paradigm. Data collection techniques were carried out through literature studies of classical and modern interpretations and literature, interviews with local religious and cultural figures, and observation of da'wah activities in various majelis taklim and Islamic boarding schools in Pamekasan. Data analysis was carried out using analysis techniques, namely data reduction, data presentation, and conclusion drawing. The results of this study show that the Makkiyah verses emphasize the values of monotheism, justice, and spiritual liberation, while the Madaniyah verses emphasize aspects of law, social ethics, and community strengthening. These values are proven to be relevant in building an inclusive Pamekasan da'wah model, rooted in local culture and oriented towards peaceful Islamic social transformation.